Compendium of veterinary products - Bayley, Adrian J. (North American Compendiums Inc., 1991)
Comprehensive listing of animal health products. Includes an alphabetical index of manufacturers and their products, an alphabetical cross-reference of ingredients and brand names, product category index, anthelmintic and parasiticide charts, product monographs, and alphabetical index of products